The Strategy of Soybean Development on Dryland Agroecosystem in Gunungkidul Regency, D.I. Yogyakarta, Indonesia - Suswatiningsih, Tri Endar; Anshori, Arif (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2023)
Soybean is a highly nutritious and strategic food. The harvested area and production of soybeans tend to decrease, not sufficient for national needs, which must be met through imports. Breakthroughs are needed to develop soybean, with specific strategies to adapt to particular conditions, including in Gunungkidul Regency. This study aimed to reveal the soybean development strategies in the dryland agroecosystem in Gunungkidul Regency. Survey and interview methods were used in this research, supported by secondary data analysis and data from the previous year's research. The correlation analysis was used to determine the decrease in harvested area. Other data were analyzed descriptively. The results showed a significant decline in soybean harvested area between 2009 to 2020. The soybean development strategy is area-based, from upstream to downstream, involving both main soybean products and by-products. Soybean planting was carried out in the first, second and third growing seasons, using site-specific soybean cultivation technology, providing seeds through the Jabalsim System supported by irrigation. Policies are needed within the organization's scope, rules, guidance and protection. The final results of this research are embodied in the form of an area-based soybean development diagram in Gunungkidul Regency, which can be used as a development reference.